Het verhaal achter het oude testament. - Bowker, John; Bowker, John; Coltman, Sarah; Posthuma, Roelof (Tielt : Kok, 1999)
Verzamelboek verschenen in 31 losse deeltjes in De Morgen en gebundeld in een map
en andere
boek